1990
DOI: 10.1111/j.1471-4159.1990.tb04946.x
|View full text |Cite
|
Sign up to set email alerts
|

Biexponential Kinetics of (R)‐α‐[3H]Methylhistamine Binding to the Rat Brain H3 Histamine Receptor

Abstract: The H3 histamine receptor is a high-affinity receptor reported to mediate inhibition of CNS histidine decarboxylase activity and depolarization-induced histamine release. We have used (R)-alpha-[3H]methylhistamine, a specific, high-affinity agonist, to characterize ligand binding to this receptor. Saturation binding studies with rat brain membranes disclosed a single class of sites (KD = 0.68 nM; Bmax = 78 fmol/mg of protein). Competition binding assays also yielded an apparently single class of sites with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…In this study we Leff, 1988;Leff et al, 1990 (Arrang et al, 1987;West et al, 1990;Kilpatrick & Michel, 1991 In summary, this study demonstrates that activation of H3 receptors within the guinea-pig ileum, can inhibit NANC contractions elicited by electric field stimulation: the NANC contraction is probably mediated by substance P acting at neurokinin NK1 receptors. In addition, we have identified an irreversible antagonist at H3 receptors within this preparation and as such this compound should become a useful tool for both in vivo and in vitro study of H3 receptors.…”
Section: Discussionmentioning
confidence: 95%
“…In this study we Leff, 1988;Leff et al, 1990 (Arrang et al, 1987;West et al, 1990;Kilpatrick & Michel, 1991 In summary, this study demonstrates that activation of H3 receptors within the guinea-pig ileum, can inhibit NANC contractions elicited by electric field stimulation: the NANC contraction is probably mediated by substance P acting at neurokinin NK1 receptors. In addition, we have identified an irreversible antagonist at H3 receptors within this preparation and as such this compound should become a useful tool for both in vivo and in vitro study of H3 receptors.…”
Section: Discussionmentioning
confidence: 95%
“…The possibility that the lack of changes in H 3 receptors was due to a non-specific labeling by [ 3 H]-R-α-methylhistamine was ruled out since previous studies in rat brain using [ 3 H]-R-α-methylhistamine have shown that this radioligand binds with high affinity to a specific binding site, considered as the histamine H 3 receptor (Arrang et al 1987West et al 1990a). Furthermore, in the present study, the specificity of [ 3 H]-R-α-methylhistamine binding in rat brain was confirmed by both the saturation analysis and the autoradiography assay.…”
Section: Discussionmentioning
confidence: 99%
“…Membranes were prepared by the method of West et al (1990a) with slight modifications. Briefly, each individual brain sample was homogenized in 30 volumes (wt/vol) of ice-cold 50 mM Tris-HCl buffer (TRIZMA hydrochloride; Sigma Chemical Co., St. Louis, Mo., USA; pH 7.5), with five up-and-down strokes of the glass-Teflon pestle.…”
Section: Methodsmentioning
confidence: 99%
“…When used at nanomolar concentrations, essentially all of the specific binding of this ligand is to H3 receptors (KD =0.7 nM). Two subpopulations of H3 receptors exist in brain tissue membranes [5,6]. Based on the rank order of potencies for several antagonists, these were designated H3A and H3B.…”
Section: Introductionmentioning
confidence: 99%